2017
DOI: 10.1038/s41467-017-01880-y
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of chemistry at a point through restructuring and catalytic activation at anchored nanoparticles

Abstract: Metal nanoparticles prepared by exsolution at the surface of perovskite oxides have been recently shown to enable new dimensions in catalysis and energy conversion and storage technologies owing to their socketed, well-anchored structure. Here we show that contrary to general belief, exsolved particles do not necessarily re-dissolve back into the underlying perovskite upon oxidation. Instead, they may remain pinned to their initial locations, allowing one to subject them to further chemical transformations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
162
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 43 publications
8
162
1
Order By: Relevance
“…16 Tsekouras et al investigated exsolution of nickel (Ni) and iron (Fe) doped La 0.4 Sr 0.4 TiO 3Àd cathodes for SOFC applications; they showed that the metallic nanoparticles Ni 0 or Fe 0 can exsolve from the parent perovskite leading to signicant performance enhancement. 14 Neagu et al showed that a cobalt (Co)-Ni spinel can exsolve from a La 0.7 Ce 0.1 Co 0.3 Ni 0.1 Ti 0.6 O 3Àd perovskite and these nanoparticles exhibit high activity towards CO oxidation at temperatures as low as 500 C. 17 Furthermore, Liu et al investigated CO 2 electrolysis showing that a Fe-Ni alloy can exsolve from a La 0.6 Sr 0.4 Fe 0.8 Ni 0.2 O 3Àd porous electrode and the presence of this alloy results in low electrode polarization resistance at temperatures around 850 C. 18 The role of A-site deciency on Ni 0 exsolution from Ni doped La 0.7 Sr 0.3 CrO 3Àd oxides has also been reported in; 19 this study showed that the introduction of 10% A-site deciency results in more Ni 0 on the surface and hence higher performance can be achieved in H 2 and H 2 /H 2 S environments. 19 To the best of our knowledge, the only work that investigated exsolution in ceramic membranes was performed by Paparguriou 20 In this work, however, only the oxygen loss (reduction) as a function of temperature in 5% H 2 (argon balance) and the electronic conductivity of the materials in the same gas environment at equilibrium were reported together with the Ni 0 particle morphology; no O 2 permeation kinetics measurements were conducted to evaluate the performance and stability of the aforementioned materials under conditions of interest to different chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16 Tsekouras et al investigated exsolution of nickel (Ni) and iron (Fe) doped La 0.4 Sr 0.4 TiO 3Àd cathodes for SOFC applications; they showed that the metallic nanoparticles Ni 0 or Fe 0 can exsolve from the parent perovskite leading to signicant performance enhancement. 14 Neagu et al showed that a cobalt (Co)-Ni spinel can exsolve from a La 0.7 Ce 0.1 Co 0.3 Ni 0.1 Ti 0.6 O 3Àd perovskite and these nanoparticles exhibit high activity towards CO oxidation at temperatures as low as 500 C. 17 Furthermore, Liu et al investigated CO 2 electrolysis showing that a Fe-Ni alloy can exsolve from a La 0.6 Sr 0.4 Fe 0.8 Ni 0.2 O 3Àd porous electrode and the presence of this alloy results in low electrode polarization resistance at temperatures around 850 C. 18 The role of A-site deciency on Ni 0 exsolution from Ni doped La 0.7 Sr 0.3 CrO 3Àd oxides has also been reported in; 19 this study showed that the introduction of 10% A-site deciency results in more Ni 0 on the surface and hence higher performance can be achieved in H 2 and H 2 /H 2 S environments. 19 To the best of our knowledge, the only work that investigated exsolution in ceramic membranes was performed by Paparguriou 20 In this work, however, only the oxygen loss (reduction) as a function of temperature in 5% H 2 (argon balance) and the electronic conductivity of the materials in the same gas environment at equilibrium were reported together with the Ni 0 particle morphology; no O 2 permeation kinetics measurements were conducted to evaluate the performance and stability of the aforementioned materials under conditions of interest to different chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…in three-way catalytic converters [1]. Recently, it has been shown that the exsolution of base metal nanoparticles from perovskite oxides may unlock superior catalytic activity towards the CO oxidation reaction [2]. For example, exsolved nickel (Ni) nanoparticles can exhibit nominal turnover frequencies (nTOF, number of CO molecules converted to CO 2 per second, per exposed metal atom site) of the order of hundreds s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The later could be explained by the stability of LSAF material in 5% H 2 /N 2 . The effect of reducing atmosphere and electric field in LSAF materials is suggested in the following defect equilibria (8) and (9).…”
Section: Discussionmentioning
confidence: 99%
“…The modified perovskite oxides with metal nanoparticles on the surface have been widely studied as catalytic materials in few chemical and electrochemical processes, such as solid oxide fuel cells (SOFCs) [3,4], electrolyzers (SOECs) [5], and automotive emission control [2,6,7]. The increased surface area of the oxides with metal nanoparticles enhances the overall catalytic activity by providing a large amount of active sites on the surface and potential synergistic effects on the interface between the metal and oxide phases [8,9]. The material performance has been improved by decorating precious metal nanoparticles on the oxide surface as active catalysts through a chemical deposition process such as infiltration or electrodeposition [2,10].…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation